The Effect of Transformational Leadership Style on the Sustainable Performance of manufacturing Industry in Iraq: The mediating role of Social Responsibility - Mohammed, Raghad (Journal of Economic Development, Environment and People, 2023)
This study aimed to examine the mediating role of social responsibility on the relationship between transformational leadership Style and the sustainable performance of manufacturing industry in Iraq. To achieve this objectives the study used descriptive analytical approach through develop questionnaire to collect data from the sample which consists (357) managers who work in manufacturing industry in Iraq. A total of (340) suitable questionnaire were retrieved for statistical analysis, the study used Statistical Package for the Social Sciences software (SPSS. 25) and Structure Equation Model (SEM) to analyses the collecting data and test the hypothesis. The study results showed that, there is impact of transformational leadership Style on the sustainable performance of manufacturing industry in Iraq, there is impact of transformational leadership Style on the social responsibility of manufacturing industry in Iraq, there is impact of social responsibility on the sustainable performance of manufacturing industry in Iraq, and there is mediating role of social responsibility on the relationship between transformational leadership Style and the sustainable performance of manufacturing industry in Iraq. In light of these findings the study recommended that In order to be more general, the next research has to involve obtaining data from other organizations in another sector in Iraq.